The impact of Brazilian samba on balance and quality of life of individuals with Parkinson’s disease - Fonseca, Líria Cruz (2021)
This non-randomized clinical trial aimed to analyze the impact of the Brazilian samba training protocol on the balance and quality of life of people with Parkinson’s disease. Forty-seven individuals participated, with a mean age of 68 ± 9.3 years-old, 24 from the control group (CG) and 23 from the experimental group (EG). The CG was formed by those who did not participate in the intervention, and the EG by individuals who participated in the Brazilian samba dance protocol. This study was divided into pre-intervention (before 12 weeks) and post-intervention (after 12 weeks) with a questionnaire consisting of: Mini Mental State Examination (MMSE); Unified Parkinson’s Disease Rating Scale (UPDRS); Quality of life (PDQ-39); Berg’s Balance Scale; Perception of perceived changes. The results point to a significant improvement after the intervention in the UPDRS (p < 0.001) and balance (p = 0.006) of the EG; in the quality of life of the EG after intervention in the mobility (p = 0.009) and total (p = 0.034) domains; and in the post-intervention period in the cognitive (p = 0.025) and communication (p = 0.032) domains of the EG and CG. Thus, it is concluded that the Brazilian samba rhythm has been shown to be effective in improving the total UPDRS, balance and quality of life, as well as in mobility, cognition and communication.